Lamb Performance on Island Pastures in Northern Norway - Lind, Vibeke; Holand, Øystein; Haugen, Finn-Arne; Steinheim, Geir (Frontiers in Veterinary Science, 2020)
The Norwegian sheep industry is based on utilization of ‘free’ rangeland pasture resources. Use of mountain pastures is dominating, with about 2 million sheep grazing these pastures during summer. Regional challenges related to e.g. loss of sheep to large carnivores make farmers think differently. The Norwegian coastline is among the longest globally and is scattered with islets and islands. Alone along the coast of Nordland county, it is estimated more than 14,000 islands. Use of islands for summer pasture is an alternative but there is a limited knowledge about such a management system. In this study, we examined lambs’ average growth rate on island pastures at the coast of Norway. In total 230 lambs on three islands (Sandvær, Sjonøya and Buøya), with varying pasture quality and stocking rate, for three years (2012, 2013 and 2014) were included. At Sandvær as much as 92% of the island was characterized as Very Good grazing value while at Sjonøya and Buøya only 15%, respectively, was characterized as Very good. We found an average daily lamb growth rate of 0.320 kg d-1. Lambs on Sandvær had a higher growth (p < 0.05) than those on Sjonøya and Buøya, and lambs’ average growth was significantly lower (p < 0.05) in 2013 compared to 2012 and 2014. We conclude that with a dynamic and adaptive management strategy there is a potential to utilize islands for sheep grazing during summer.